PENGEMBANGAN POTENSI SUMBER DAYA LAUT MELALUI PELATIHAN KERUPUK KERANG LOKAN DI RAJA AMPAT - Edwar, Rizka Cintya; Damanik, Lisa Gresti Sella; Mangopo, Yuni Riskita; Landjang, Xenia Irene Sandy; Toii, Indra Eka Wardana; Azelya, Iis (Batara Wisnu : Indonesian Journal of Community Services, 2025)
The community service activity with the theme "Training on Making Crackers from Locan Shellfish" was carried out in October 2024 in Kampung Gamta, Misol Barat District, Raja Ampat Regency. The purpose of this activity is to develop the potential of marine resources, particularly locan shellfish, which has so far been used mainly as a supplementary food, by processing it into crackers made from locan shellfish. This training involved 17 participants and was conducted using a systematic approach with the PDCA (Plan-Do-Check-Act) method, which consists of planning, implementation, evaluation, and follow-up stages. Through this training, it is hoped that the community will develop skills in producing crackers, create a local flagship product, and open new business opportunities that have the potential to increase household income in Kampung Gamta.